2006
DOI: 10.3168/jds.s0022-0302(06)72303-7
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Near-Infrared Reflectance Spectroscopy to Predict Nutrient Composition and In Vitro Digestibility of Total Mixed Rations

Abstract: Total mixed ration (TMR) samples (n = 110) were analyzed for dry matter (DM), crude protein (CP), soluble CP, neutral detergent fiber (NDF), NDF CP, starch, ash, fat, total ethanol-soluble carbohydrate, and nonfiber carbohydrate (NFC). Rapidly and slowly degraded and undegraded in situ CP fractions and in vitro DM, organic matter, and NDF digestibility were determined on each TMR. The TMR were scanned using near-infrared reflectance spectroscopy (NIRS); spectra were retained with NIRS calibration and cross-val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
49
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 19 publications
9
49
1
Order By: Relevance
“…NIRS calibration development must be based on widely-accepted analytical procedures, but these are frequently poorly-defined chemically and sometimes do not relate to spectroscopic data (Shenk & Westerhaus, 1994). Theoretically, inorganic substances do not absorb energy in the near infrared (NIR) region but some papers have demonstrated that NIRS can reliably predict the ash content of feed (Deaville & Flinn, 2000;Mentink, Hoffman, & Bauman, 2006;Osborne, 2001;Park, Agnew, Gordon, & Steen, 1998;Pérez-Marín, Garrido-Varo, Guerrero-Ginel, & Gómez-Cabrera, 2004). Since ash content cannot be directly measured by NIRS, it is assumed that it is predicted by correlation with the total amount of organic compounds and water present because of the large number of wavelengths used in the process of calibration development that give significant information (Clarke, Mayland, & Lamb, 1987;Frankhuizen, 2001;Garnsworthy, Wiseman, & Fegeros, 2000;Osborne, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…NIRS calibration development must be based on widely-accepted analytical procedures, but these are frequently poorly-defined chemically and sometimes do not relate to spectroscopic data (Shenk & Westerhaus, 1994). Theoretically, inorganic substances do not absorb energy in the near infrared (NIR) region but some papers have demonstrated that NIRS can reliably predict the ash content of feed (Deaville & Flinn, 2000;Mentink, Hoffman, & Bauman, 2006;Osborne, 2001;Park, Agnew, Gordon, & Steen, 1998;Pérez-Marín, Garrido-Varo, Guerrero-Ginel, & Gómez-Cabrera, 2004). Since ash content cannot be directly measured by NIRS, it is assumed that it is predicted by correlation with the total amount of organic compounds and water present because of the large number of wavelengths used in the process of calibration development that give significant information (Clarke, Mayland, & Lamb, 1987;Frankhuizen, 2001;Garnsworthy, Wiseman, & Fegeros, 2000;Osborne, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These relationships have been used as predictors of various OM components [62,63] with universal calibration equations developed from large (>100) sample sets. The prediction accuracy is dependent on a significant and strong correlation (R 2 > 0.85) of the spectral data and wet chemistry [64]. Robust NIRS calibrations have been developed using largely C4 forages for the prediction for iNDF [65].…”
Section: Alternative Assessment Of Indfmentioning
confidence: 99%
“…Recently, Mayer et al [14] suggested near infrared spectroscopy (NIRS) as an alternative technique to determine the BMP FM . NIRS is widely used in feed and food quality monitoring [19][20][21][22][23][24][25][26] and is accepted since many years as routine method for determining forage quality parameters of various crops. In the bioenergy sector NIRS has been applied to estimate sulphur content in biodiesel [27], for predicting digestibility of maize silage [28][29][30] and fermentation parameters of silages [31], and for the assessment of in situ degradability parameters of crude protein and dry matter characteristics [32,33].…”
Section: Introductionmentioning
confidence: 99%